A Method for Scriptio Continua Management on the Transliteration to the Balinese Script - G. Indrawan, I W. Sutaya, K. U. Ariawan, M. S. Gitakarma, I G. Nurhayata, I K. Paramarta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research proposed a method for scriptio continua management on the learning application-based transliteration to the Balinese Script. It has not been conducted yet and is important since the proposed method eases the learning of the Balinese Script as the transliteration output. This research is a technological preservation effort to the endangered Balinese local language knowledge in Indonesia through the multi-discipline collaboration between Engineering (especially on applied Computer Science) and Language discipline. The proposed method took care of two related aspects, i.e.: (1) The Balinese Script uses scriptio continua as a style of writing without spaces, so do its transliteration result to the Balinese Script; and (2) A switching management between scriptio continua and non-scriptio continua style is needed by the learning application for the ease of learning through the visual analysis of the transliteration output which is the Balinese Script. This study was conducted on the pioneering web-based transliteration learning application, BaliScript, with the Latin text as the input and the Balinese Script as the output. Through the experiment, the proposed method gave the expected transliteration result on scriptio continua management, which can switch between three styles of writing, i.e.: (1) scriptio continua; (2) unconditional non-scriptio continua; and (3) conditional non-scriptio continua.